DIGITAL CITIZENSHIP SKILLS SURVEY IN HIGH SCHOOL: SURVEI KETERAMPILAN KEWARGANEGARAAN DIGITAL DI SEKOLAH MENENGAH ATAS - Nisrina Nurul Insani; Aim Abdul Karim; Kokom Komalasari; Rahmat Rahmat (SOSIOEDUKASI, 2025)
This research is motivated by the need to understand the digital citizenship skills of high school students as part of strengthening Global Citizenship Education and integrating the Pancasila Education curriculum. The purpose of the research is to measure students' digital citizenship skills, identify strengths and weaknesses in each dimension, and provide recommendations for curriculum development. The method used was a quantitative survey with 896 respondents from public high schools in the city of Bandung. The instrument in the form of a Likert scale questionnaire covers four dimensions: Digital Access, Digital Communication, Digital Etiquette, and Digital Rights & Responsibilities. The results showed that students' skills were in the medium to high category, with strengths in the aspects of digital security and polite communication, while weaknesses were seen in the creativity of positive content and the ability to explain ideas clearly. These findings underscore the importance of learning that emphasizes not only technical literacy, but also critical communication, empathy, and productive contributions in the digital space. As a result, the results of this study provide an empirical basis for schools and policymakers in strengthening the Pancasila Education curriculum based on deep learning. The next recommendation is the need for longitudinal research and curriculum interventions to optimize the role of students as critical, ethical, and participatory digital citizens.